Sensitization to dust mite defines different phenotypes of asthma: A multicenter study. Issue 7 (7th September 2017) - Ruggieri, Silvia; Drago, Gaspare; Longo, Valeria; Colombo, Paolo; Balzan, Martin; Bilocca, David; Zammit, Christopher; Montefort, Stephen; Scaccianoce, Gianluca; Cuttitta, Giuseppina; Viegi, Giovanni; Cibella, Fabio; et al.
Abstract: Background: Indoor allergens are risk factors for asthma: Thus, the characterization of indoor air quality is important for studying environment–health relationships in children. In particular, Dermatophagoides pteronyssinus is the dominant allergen for asthma. We cross‐sectionally investigated the relationships among respiratory symptoms and function, airway inflammation, allergen sensitization, and indoor allergen concentration. Methods: One hundred and thirty‐two children aging 10‐14 years and living in a Southern Mediterranean area were evaluated by parental questionnaires. Spirometry, exhaled nitric oxide (FeNO), skin prick tests, total, and specific serum IgE analyses were performed along with the evaluation of home dust samples for the content in Der p 1 allergen. Three clusters were created on the basis of the presence/absence of wheeze in the last 12 months (Wh12m) and Der p 1‐specific IgE level. Results: Cluster 1 (Wh12m+/high Der p 1 IgE) presented higher FeNO and poorer pulmonary function (lower FEV1 and FEF25%‐75% ), while its symptom score was not different from Cluster 2 (Wh12m+/low Der p 1 IgE). Cluster 3 (Wh12m−/low IgE) showed the lowest FeNO values and pulmonary function similar to Cluster 2. Within Cluster 1, both Der p 1‐specific IgE and FeNO were positively correlated with dust Der p 1. Conclusions: Similar asthma phenotypes may occur in children despite differences in their atopic state. In atopic children, sensitizing allergens in the indoor environment may increase airway inflammation worsening pulmonary function. Moreover, environmental exposures may contribute to the development of asthma‐like symptoms also in the absence of atopic sensitization, thus contributing to asthma overdiagnosis.